1996
DOI: 10.1073/pnas.93.5.2025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in vitro correction of alpha-L-iduronidase deficiency (Hurler syndrome) in human bone marrow.

Abstract: Allogeneic bone marrow transplantation is the most effective treatment for Hurler syndrome but, since this therapy is not available to all patients, we have considered an alternative approach based on transfer and expression of the normal gene in autologous bone marrow. A retroviral vector carrying the full-length cDNA for a-L-iduronidase has been constructed and used to transduce bone marrow from patients with this disorder. Various gene-transfer protocols have been assessed including the effect of intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 26 publications
1
22
1
2
Order By: Relevance
“…Along these lines, lymphocytes from patients with Hunter syndrome were corrected endogenously for the enzymatic defect by retroviral-mediated gene transfer and cell-tocell enzyme activity transmission occurred (23). Another recent study demonstrated sustained long-term expression and secretion of a-L-iduronidase, another lysosomal enzyme, in transduced human stem/progenitor cells (24). This further demonstrates the potential for metabolic cooperativity for many diseases of this type.…”
Section: Discussionmentioning
confidence: 91%
“…Along these lines, lymphocytes from patients with Hunter syndrome were corrected endogenously for the enzymatic defect by retroviral-mediated gene transfer and cell-tocell enzyme activity transmission occurred (23). Another recent study demonstrated sustained long-term expression and secretion of a-L-iduronidase, another lysosomal enzyme, in transduced human stem/progenitor cells (24). This further demonstrates the potential for metabolic cooperativity for many diseases of this type.…”
Section: Discussionmentioning
confidence: 91%
“…17 Lenhanced green fluorescent protein (L-EGFP) was derived by replacing the IDUA complementary DNA in Lid with a complementary DNA encoding L-EGFP. Cells (30%-40% confluent) were transduced using cell-free retroviral supernatant supplemented with 2 g/mL polybrene.…”
Section: Transduction Of Mscsmentioning
confidence: 99%
“…21 The D 37 values obtained for temozolomide and mitozolomide, as well as for another chloroethylating agent, chlorozotocin (Table 2), demonstrated that the retroviral delivery and expression of hATPA/GA can significantly protect human haemopoietic cells against the toxicity of a wide + cells were transduced with LhATPA/GA, exposed to increasing temozolomide concentrations in the presence (10 m) or absence of O 6 -beG and the survival of the GM-CFC determined ( Figure 2a). As controls, cells were transduced with a retrovirus harbouring the ␣-iduronidase cDNA (LID) 20 and were treated identically and in parallel with LhATPA/GAtransduced cells. Under conditions in which a transduction efficiency of 70% was achieved, as determined by PCR, CD34…”
Section: Protection Of Human Erythroleukaemic Progenitors (K562) From Omentioning
confidence: 99%